1988
DOI: 10.1111/j.1559-3584.1988.tb01498.x
|View full text |Cite
|
Sign up to set email alerts
|

Ship Em Design Technology

Abstract: This paper describes the design procedure and engineering design tools used for Navy shipboard exterior RF communication system design. The approach is an iterative process by which candidate RF system designs can be analyzed to determine their relative desirability. Several computer codes have been developed for designing the exterior RF communication systems for Navy ships. The software design aids consist of two packages, one for antenna modeling (such as the NEC‐Method of Moments, NEC‐Basic Scattering, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The challenge to the integration of antennas in a topside design is that (Li et al 1988): ■ All factors influencing an antenna system performance must be identified before an antenna site can be selected.…”
Section: Technical Approachmentioning
confidence: 99%
“…The challenge to the integration of antennas in a topside design is that (Li et al 1988): ■ All factors influencing an antenna system performance must be identified before an antenna site can be selected.…”
Section: Technical Approachmentioning
confidence: 99%
“…(6) It can preserve useful knowledge, manage the data bases, remember similar ship experiences, and never overlook any relevant rules. (7) It can consistently produce solutions at the same level. The permanence is not related to its use.…”
Section: Critical Design Features Of Cleermentioning
confidence: 99%
“…NEC includes the NEC-method of moments (NEC-MoM), NEC-basic scattering, and NEC-reflector antenna codes (Li, et al, 1988). All these codes have been validated and extensively documented.…”
Section: Numerical Electromagnetic Codementioning
confidence: 99%
“…This section describes the design procedure used for Navy shipboard exterior radio frequency (RF) communication system design (Li, Logan, & Rockway, 1988). The approach is an iteration process by which candidate RF system designs can be analyzed to determine their relative desirability.…”
Section: Ship Em Design Proceduresmentioning
confidence: 99%